ADVANCED COMPUTATIONALMETHODS FOR COMPLEX SIMULATION OF THERMAL PROCESSES IN POWER ENGINEERING - Risto V. Filkoski; Ilija J. Petrovski (Problems of the Regional Energetics)
The overall frame and principal steps of complex numerical modelling of thermal processes in power boiler furnaces on pulverised coal with tangential disposition of the burners are presented in the paper. Computational fluid dynamics (CFD) technique is used as a tool to perform comprehensive thermal analysis in two test cases. The methodology for creation of three-dimensional models of boiler furnaces is briefly described. Standard steady k- model is employed for description of the turbulent flow. The coupling of continuity and momentum is achieved by the SIMPLEC method. Coal combustion is modelled by the mixture fraction/probability density function approach for the reaction chemistry, with equilibrium assumption applied for description of the system chemistry. Thermal radiation is computed by means of the simplified P-N model, based on expansion of the radiation intensity into an orthogonal series of spherical harmonics.Comparison between the simulation predictions and available site measurements leads to a conclusion that the model produces realistic insight into the furnace processes. Qualitative agreement of the results indicates reasonability of the calculations and validates the employed sub-models. The described test cases and other experiences with CFD modelling stress the advantages over a purely field data study, such as the ability to quickly and cheaply analyse a variety of design options without actually modifying the object and the availability of significantly more data to interpret the results.